Strategic Influence in Focus: Assessing the Roles of Defense Expenditures, Foreign Capital, Political Stability, and Energy Sustainability in Geopolitical Dynamics - Khan, Muhammad Bahar; Naseem, Imran; Hamidi, Ahmad; Jabor, Mohd Khata; Bandar, Nur Fatihah Abdullah; Zaman, Khalid (International Journal of Energy Economics and Policy, 2024)
The study examines Pakistan’s geopolitical relevance by examining its military expenditure, FDI, political stability, energy production, and trade openness. The research utilizes a two-stage least squares (2SLS) regression model for 1996 Q1-2022 Q4 to account for explanatory variable endogeneity for credible estimations. The findings show that military expenditure and political instability lower Pakistan’s geopolitical relevance, as measured by foreign aid. Rising military spending and political upheaval may deter foreign donations due to regional security and resource allocation concerns. Economic resilience and global integration are connected to energy production, trade openness, and geopolitical importance. Therefore, Pakistan needs them to boost its international standing. The analysis also demonstrates that less foreign assistance is connected with higher FDI inflows, which may increase economic independence. These findings, which support the “guns versus butter” paradigm and economic interdependence, may inspire Pakistan’s geopolitical dynamics. This study provides facts on a country’s economic, political, and strategic drivers of geopolitical relevance. These findings may assist Pakistan’s authorities in finding a balance between military and economic measures to boost its global status.